2007
DOI: 10.1002/ep.10180
|View full text |Cite
|
Sign up to set email alerts
|

Removal of boron dissolved in water

Abstract: The study aimed to investigate boron adsorption on activated carbon, activated carbon impregnated with different substances, activated alumina, zirconium dioxide and silica‐aerosil. The removal of boron from water was carried out in static and dynamic systems. Isotherms for boron adsorption from model aqueous solutions on various adsorbents were applied and Langmuir constants were calculated. The results indicate that the application of the impregnants increases the ability of activated carbon to adsorb boron.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 20 publications
3
20
1
Order By: Relevance
“…The monolayer sorption capacity (q m = 30 mg g -1 ) as shown in Table 2, was found to be higher than most of the reported sorption capacities (1.00 -2.20 mg g -1 ) (Kluczka et al 2007; Liu and Ismanto 2014).…”
Section: Kinetic Isotherm and Statistical Analysesmentioning
confidence: 84%
See 1 more Smart Citation
“…The monolayer sorption capacity (q m = 30 mg g -1 ) as shown in Table 2, was found to be higher than most of the reported sorption capacities (1.00 -2.20 mg g -1 ) (Kluczka et al 2007; Liu and Ismanto 2014).…”
Section: Kinetic Isotherm and Statistical Analysesmentioning
confidence: 84%
“…PS-PVA beads have not been applied to treat boron-contaminated wastewater under fixed-bed operation, and it can be concluded that the synthesized PS-PVA is efficacious and outperforms most of the reported adsorbents for boron removal from aqueous A c c e p t e d M a n u s c r i p t 4 solutions (Man et al 2012;Kluczka et al 2007;Liu and Ismanto 2014). Using response surface methodology (RSM) in this study is to evaluate the performance of the adsorbent under column operation, to decrease the number of column runs, to examine the combined effects of independent variables on the breakthrough curve, and finally to develop a statistical expression to identify the optimum conditions for maximum boron uptake.…”
mentioning
confidence: 96%
“…For adsorbent preparation, clinoptilolite and ZrO 2 were used. The preliminary experiments showed that amorphous ZrO 2 had the ability to adsorb boron in contrast to the crystalline form of ZrO 2 , which showed no affinity for oxoborate ions [41]. Therefore in the present study, amorphous ZrO 2 prepared in our laboratory was used for the first time as modifier of clinoptilolite to adsorb boron.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, high costs of chemical substances, as well as the costs of sludge utilization and disposal make this process of boron elimination inadvisable in many cases [8,9]. Activated carbon, impregnated activated carbon and silty materials, due to their high sorption capacity, proved to be ineffective and unprofitable when used in a large scale [10,11]. A liquid-liquid extraction technology offers a possibility of retrieving boron for market purposes from industrial wastewater, but it is only profitable when the initial concentration of boron in solution is at least 3 g/L [12,13].…”
Section: Introductionmentioning
confidence: 99%